Are you there God? It's me, Margaret - Blume, Judy. (New York : Yearling, 1986)
Twelve-year-old Margaret, whose parents are Jewish and Christian, tries to choose a religion while struggling with the changes of adolescence.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
4.1.
4.1
3-6
Keywords: Religion -- Juvenile fiction; Teenage girls -- Juvenile fiction; Religion -- Fiction; Teenage girls -- Fiction; Girls -- Fiction; Religion -- Fiction; Teenagers -- Fiction